Improved frictional behavior of SiC derived carbon coating using MoS3 as a solid lubricant. (February 2016) - Liu, Fuyan; Wang, Tingmei; Wang, Qihua; Meng, Junhu; Lu, Jinjun
Abstract: Frictional behavior of carbide-derived carbon (CDC) coatings on SiC was modified by using MoS3 as solid lubricants in two forms, i.e. a powder lubricant and a lubricating additive. As the powder lubricant, MoS3 was unfavorable for the tribological behavior of CDC coatings. Moreover, its friction and wear behaviors were worse than that of MoS2 . As the lubricating additive, MoS3 was in-situ prepared within CDC coatings to obtain two kinds of CDC-MoS3 composites with different microstructures. The CDC-MoS3 composites showed lower friction than untreated CDC coatings and their tribological behavior was significantly affected by the microstructures.